Species diversity of grasses as an indicator of air quality in the wayside Grassland Community a field activity of college biology classes - Carvajal, Alberto C. (1979)
The study attempted to develop, try-out, and evaluate a field activity based on the preliminary investigation of the organism-pollution relationship in the wayside grassland community. Based on a preliminary investigation, a field activity composed of four activities was developed. The analyses of the results of the try-out and evaluation indicated positive responses of the students to the following aspects of the activity: mechanics, relevance, students' attitude towards the activity, and the feasibility of the activity. It was concluded that the field activity was worthwhile prescribing for use in college biology classes.